Pengembangan Media Gambar Berseri Berbasis Multimedia terhadap Kemampuan Membaca Bahasa Inggris Siswa Kelas V Sekolah Dasar - Nur Indah Kusumawati; Mawardi Mawardi; Nur Latifah (AS-SABIQUN, 2022)
This study aims to develop multimedia-based serial image media for fifth grade English reading skills with material for daily activities which can be useful in learning to read English in elementary schools. The method used in this research is research and development (R&D). The model used in this study uses the ADDIE model which consists of 5 stages, namely, (1) The analysis stage analyzes the needs of the primary school in question and provides solutions to existing problems, (2) The design stage is by setting goals, competency standards, syllabus. , media design design, and research instruments, (3) The development stage makes learning media and validation of learning media carried out by media experts who assess the media in the good category, and material experts who assess the material on the learning media in the good category, (4) The implementation stage is to apply learning media to class V B SD Negeri Sukasari, (5) The evaluation stage provides a questionnaire on the practicality of learning media developed for teachers in the field of English studies with practical categories and according to student responses it is very practical. And the assessment of reading English experienced an average increase from the results of the pretest and posttest.